Last visit was: 23 Apr 2024, 20:31 It is currently 23 Apr 2024, 20:31

GMAT Club Daily Prep
Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History
Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

# Is  nm^2 + nm - 12n = 0? (1) m^2 = 16 (2) m = -4

SORT BY:
Tags:
Show Tags
Hide Tags
Intern
Joined: 21 Jan 2022
Posts: 1
Own Kudos [?]: 1 [1]
Given Kudos: 6
Founder
Joined: 04 Dec 2002
Posts: 37300
Own Kudos [?]: 72861 [1]
Given Kudos: 18857
Location: United States (WA)
GMAT 1: 750 Q49 V42
GPA: 3
GMAT Club Legend
Joined: 03 Jun 2019
Posts: 5342
Own Kudos [?]: 3964 [1]
Given Kudos: 160
Location: India
GMAT 1: 690 Q50 V34
WE:Engineering (Transportation)
Intern
Joined: 12 Feb 2024
Posts: 29
Own Kudos [?]: 37 [0]
Given Kudos: 24
Is  nm^2 + nm - 12n = 0? (1) m^2 = 16 (2) m = -4  [#permalink]
Kinshook wrote:
@1992SonalAsked: Is  nm^2 + nm - 12n = 0?
Is  n(m^2 + m - 12) = 0?
Is n(m+4)(m-3) = 0?

(1)   m^2 = 16
If m = 4; n(m-4)(m+3) is NOT necessarily 0
If m=-4; n(m-4)(m+3) = 0
NOT SUFFICIENT

(2)   m = -4 n(m-4)(m+3) = 0
SUFFICIENT

IMO B

Kinshook ­I don't understand how (2) is sufficient?

If m = 4 then it makes sense because n(m-4)(m+3) = n(4-4)(4+3) = 0
but doesn't m = -4 mean n(-4-4)(-4+3) = n(-8)(-1) = 8n?
GMAT Club Legend
Joined: 03 Jun 2019
Posts: 5342
Own Kudos [?]: 3964 [1]
Given Kudos: 160
Location: India
GMAT 1: 690 Q50 V34
WE:Engineering (Transportation)
Re: Is  nm^2 + nm - 12n = 0? (1) m^2 = 16 (2) m = -4  [#permalink]
1
Kudos
helpmegmat

Quote:
Kinshook wrote:
@1992SonalAsked: Is  nm^2 + nm - 12n = 0?
Is  n(m^2 + m - 12) = 0?
Is n(m+4)(m-3) = 0?

(1)   m^2 = 16
If m = 4; n(m-4)(m+3) is NOT necessarily 0
If m=-4; n(m-4)(m+3) = 0
NOT SUFFICIENT

(2)   m = -4 n(m-4)(m+3) = 0
SUFFICIENT

IMO B

Kinshook ­I don't understand how (2) is sufficient?

If m = 4 then it makes sense because n(m-4)(m+3) = n(4-4)(4+3) = 0
but doesn't m = -4 mean n(-4-4)(-4+3) = n(-8)(-1) = 8n?

­
Re: Is  nm^2 + nm - 12n = 0? (1) m^2 = 16 (2) m = -4  [#permalink]
Moderator:
Math Expert
92883 posts